The Influence of the Discovery Learning Model on Students' Concept Understanding and Learning Independence in Science Learning in Elementary Schools - Juriyah, Juriyah; Raharjo, Tri Joko; Pramono, Suwito Eko (Peneliti.net, 2025)
Natural Science (IPA) learning in Elementary Schools plays an important role in building the foundation of scientific thinking and students' science process skills. However, conventional and teacher-centered learning practices often hinder students' conceptual understanding and learning independence. This study aims to analyze the influence of the Discovery Learning model on conceptual understanding and learning independence in science learning in Elementary Schools. The method used is a systematic literature review with a qualitative descriptive approach to a number of relevant scientific articles. The results of the study show that Discovery Learning is consistently able to improve conceptual understanding through exploration, observation, and conclusion activities, and encourage learning independence through active student involvement in the learning process. This model also supports the development of critical, creative, collaborative, and communicative (4C) thinking skills. Despite implementation challenges, such as time constraints and teacher readiness, Discovery Learning remains an effective and relevant approach to be applied in science learning in the Merdeka Curriculum era. This study provides theoretical and practical contributions in efforts to improve the quality of active, meaningful, and student-centered science learning.